Caractérisation chimique, activités antiradicalaire et antibactérienne des extraits de l’écorce de racine de Cochlospermum planchoni du Bénin - KOUDORO, YAYA ALAIN; Dèdomè, L; S. Oronce; YOVO, Mahudjro; AGBANGNAN, DOSSA COKOU PASCAL; TCHOBO, PAUL FIDÈLE; ALITONOU, GUY ALAIN; AVLESSI, FÉLICIEN; SOHOUNHLOUE, KOKO CODJO DOMINIQUE (My University, 2014)
Herbal medicines are the most widely used especially in rural areas to solve problems of human and animal health Saharan average. This paper reports the results of the chemical and biological studies of the root bark of Cochlospermum planchoni used by farmers in Benin in the treatment of gastrointestinal diseases of animals. Results obtained, it appears that the root bark of C. planchoni is rich in secondary metabolites such as flavonoids, polyphenols, tannins, anthocyanins, leucoanthocyanins, mucilages, saponins, sterols and terpenes. Regarding the extraction yield, the binary water-ethanol (50/50) allowed to have a better (23.2%) extraction yield this of plant. As for the quantification of the polyphenols content, it is practically insensitive to the nature of the extraction solvent on crude extracts of the root bark of C. planchoni. According to the tests of antiradical activity, both fractions ethyl ether and ethyl acetate (IC50 = 1μg/ml) showed a more interesting radical scavenging activity than that of quercetin (IC50 = 3μg/ml) and BHA (IC50 = 4, 8μg/ml) which are antiradical syntheses. The results from the test of antibacterial activity show that the fractions of ethyl acetate, diethyl ether and butanol are more active than of the crude extracts of C. planchoni on the four bacterial strains used in this study.
Keywords: Cochlospermum planchoni; secondary metabolites; bactericidal; DPPH.